Re-iterating Theory in Architecture: - Gines, Leonido M. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 11, 2025)
The study of architectural theory in the Philippines is still in need of a transnational framework beyond the Vitruvian Triad that most architectural academics are wont to teach. Many Southeast Asian architectural institutions, including those in the Philippines have already embedded in their curricula and in teaching sessions in the design studios, modern and contemporary discourses that expand the issues and problems of the built environment. Beyond Vitruvian principles, neoclassical or modern references, necessitating the need to study architectural theory both intra-disciplinarily and beyond the boundaries of the architecture domain requires new problemsolving heuristics and conceptual devices that absorb local and subjugated knowledge. The Philippine experience struggles with the synergy of architecture as a problem-solving practice and architecture as a theoretical discourse. One of the more obvious reasons for such struggle is the dearth of transnational framework or literature, and its dissemination to Philippine architectural academia. There is an urgent need to expand the theoretical and creative knowledge of architecture students now that institutions are preparing for an overhaul of architecture education in the Philippines, and the region of Southeast Asia at large. This region, despite its multiple identities and heterogeneous differences, shares qualities in its geolocational, linguistic and even colonial experience that can inform or even transform pedagogical frameworks. Necessary to this preparation are new transdisciplinary frameworks that can reassess both form and content in architectural design theory. This paper sees this overhaul challenge as an opportunity to and attempt at proposing a provincialized and transnational framework of architectural history for reiterating theory in the study of architecture.